Efficient removal of organic and bacterial pollutants by Ag-La0.8Ca0.2Fe0.94O3-δ perovskite via catalytic peroxymonosulfate activation - Chu, Y.; Tan, X.; Shen, Zhangfeng; Liu, Pengyun; Han, Ning; Kang, Jian; Duan, Xiaoguang; Wang, Shaobin; Liu, Lihong; Liu, Shaomin (Elsevier BV, 2018)
© 2018 Elsevier B.V. Removal of toxic organics and bacterial disinfection are important tasks in wastewater treatment. Most heavy metal-based catalysts for degradation of aqueous organic pollutants in heterogeneous Fenton-like processes suffer from the toxicity of leached metals. The present work reports environmentally benign systems for both degradation of organics and bacterial disinfection. Calcium substituted LaFeO 3- d perovskite was demonstrated as an efficient catalyst to activate peroxymonosulfate (PMS) for degradation of phenol, methylene blue and rhodamine 6 G. Compared to LaFeO 3- d and nanocrystal Fe 3 O 4 , the lattice oxygen vacancies in B-site cation-deficient perovskite of La 0.8 Ca 0.2 Fe 0.94 O 3 - d (LaCaFeO 3- d ) particles renders this material a greatly improved catalytic performance. Electron paramagnetic resonance (EPR) suggested that both sulfate (SO 4 [rad]–) and hydroxyl radicals ([rad] OH) played critical roles in the advanced oxidation processes. Moreover, silver doped perovskite (Ag-LaCaFeO 3- d )/PMS successfully inhibited the growth of waterborne pathogen Escherichia coli and Methicillin-resistant Staphylococcus aureus (MRSA) at a lower dose than silver ions, proving a synergetic effect between free radicals and Ag + in killing the bacteria. Therefore, Ag-LaCaFeO 3- d /PMS would be promising for practical wastewater treatment.